Pengaruh Profitabilitas dan Likuiditas terhadap Nilai Perusahaan pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2021–2025 - Dede Amanda; Aswin Akbar (Jurnal Riset Ekonomi dan Akuntansi, 2026)
This study aims to analyze the effect of profitability and liquidity on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2025 period. The study was motivated by inconsistencies in previous research results regarding the influence of profitability and liquidity on firm value. Profitability was measured using Return on Assets (ROA), liquidity was measured using Current Ratio (CR), while firm value was measured using Price to Book Value (PBV). This research employed a quantitative approach using secondary data obtained from company financial statements. The sampling technique used purposive sampling with a total sample of 9 manufacturing companies during the research period. The data analysis methods included descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, coefficient of determination test (R²), partial test (t-test), and simultaneous test (F-test) using SPSS software. The results showed that company profitability tended to be stable although several companies experienced performance fluctuations, while liquidity levels showed considerable variation among companies. Based on the partial test results, profitability (ROA) did not have a significant effect on firm value with a significance value of 0.765 (>0.05), while liquidity (CR) had a significant negative effect on firm value with a significance value of 0.011 (<0.05). Simultaneously, profitability and liquidity had a significant effect on firm value with an F-test significance value of 0.020 (<0.05). The coefficient of determination (R²) value of 0.169 indicates that profitability and liquidity were able to explain 16.9% of the variation in firm value, while the remaining 83.1% was influenced by other factors outside the study. This research is expected to contribute to the development of financial management knowledge and serve as a consideration for investors and companies in decision-making.